PENGARUH STRES DAN MOTIVASI TERHADAPKINERJA ANGGOTA PENERBANG POLRI PADA DITPOLUDARA KORPOLAIRUD BAHARKAM POLRI - Mochammad Ramdan Perdana; Yunita Wahyuningtyas (Sekolah Tinggi Manajemen IMMI, 2020)
This study aims to look at the effect of stress and motivation on the performance of members of the National Aviation Pilots on the Directorate of Politics and Human Rights Baharkam. The research method used was a survey method. The research respondents were 100 members who were being placed in the Polri Police Academy Baharkam Ditpoludara. The results of the study showed that although the Stress and Motivation variables were jointly affected by the performance of members of the National Aviation Pilots in the Indonesian Police Headquarters of the Polark. However, only partially one variable (Motivation) is significant for Polri Aviator Pilots Members at the Polri Korpolairud Baharkam Police Department, and this also makes Motivation the dominant variable. Technically, stepwise it can be seen that the motivation variable (X2) is more dominant (more instrumental) in the Performance of Polri Aviation Members in the Polytechnic Air Force Headquarters Baharkam than the Stress variable (X1).From the testing of the hypothesis shows that the significance with Alpha (Alpha) is far below 5%, thus H1 is accepted which means that there are influences of variables X1 and X2, together with Y variables or in other words performance formation variables are influenced simultaneously by stress variables and motivation. Based on these findings, the existing Motivation Factor has a very strong influence on the Performance of Polri Aviation Pilots in the Polri Police Headquarters, and improvements in the provision of continuous motivation will contribute well to improving the quality of work of Polri Aviator Pilots in the Polri Ditpoludara Baharkam Polri.As for the other variables, the member stress variable is apparently not dominant in improving the performance of members of the National Aviation Pilots in the Polri Police Headquarters Baharkam. Therefore, it is necessary to further examine whether the current program has been effective in reducing stress or vice versa.